Design, fabrication and testing of fixture for implementation of a new approach to incorporate tool tilting in friction stir welding - Awang, M. (EDP Sciences, 2014)
Friction Stir Welding (FSW) is solid-state process for joining materials by using frictional heat generated due to rotating tool along the weld line. Since its invention about two decades ago, wide spread use of FSW is still restricted due to very expensive purpose built FSW machines available in the market. As an alternative, a milling machine can be used to carry out the FSW depending on the capabilities of the machine. In cases where milling machines have a fixed head, limitation of zero degree tool tilt angle results in substantial defects (e.g. tunnel defect) in weldments. The objective of this study is to design and fabricate an adjustable-angle fixture to incorporate tool tilting in a CNC milling machine with fixed spindle head. The testing of the fabricated fixture is then carried out by running the FSW experiments at different tilt angles. Â© 2014 Owned by the authors, published by EDP Sciences.